Photovoltaic (PV) and thermo-electric energy harvesters for charging applications. (February 2020) - Saha, C.R.; Huda, M.N.; Mumtaz, A.; Debnath, A.; Thomas, S.; Jinks, R.
Abstract: Significant technical progress is currently ongoing in the field of energy harvesting technologies. This paper presents a study of both photovoltaic (PV) and thermo-electric energy harvesting techniques in the context of mobile phone applications. The paper includes performance analysis of a macro scale PV module and a thermo-electric generator (investigated under different conditions), together with a single diode electrical equivalent circuit model of the solar PV developed using MATLAB/Simulink. Additionally experimental results of the PV module are verified via simulation. To complete the study a PV module is integrated with a DC/DC adjustable converter and solar charge controller (3A CMTP02) to charge a smart mobile phone in order to assimilate charging capacity and feasibility of macro scale energy harvesting devices. Graphical abstract: Image 1 Highlights: This paper focuses on performance analysis of a solar PV and a thermoelectric generator for mobile phone applications. Present the background theory of Solar PV and Thermo-electric energy harvester and discuss the experimental results. Simulink model of solar PV was built to generate the I-V/P-V curve and the results are compared with experimental values.